Solubility Prediction of Anthracene in Non-Aqueous Solvent Mixtures Using Jouyban-Acree Model: Solubility prediction of anthracene - Jouyban, Abolghasem; Jalilzadeh, Hassan; Khoubnasabjafari, Maryam; E. Acree Jr, William (Iranian Journal of Pharmaceutical Sciences, 2006)
A quanitative structure property relationship was proposed to calculate the binary interaction terms of the Jouyban-Acree model using solubility parameter, boiling point, vapour pressure and density of solvents. The applicability of the proposed method for reproducing solubility data of anthracene in binary solvents has been evaluated using 116 solubility data sets collected from the literature. The mean percentage deviation (MPD) of experimental and calculated solubilities has been computed as a measure of accuracy and the MPD of the proposed method was 6 %. The accuracy of the method was compared with that of a previously reported method where the MPD was 12 % and the mean differences between proposed and previous methods was statistically significant.